Utilization of senorita bananas (Musa sapientum Linn.) and banana flour in banana catsup - Salle, Maria Rita S.; Acevedeo, Teresita P. (1997.)
The utilization of fully ripe Señorita bananas (Musa sapientum, Linn.) and the flour prepared from its unripe fruit as base material for banana catsup was studied. Substitution of banana pulp with banana flour was tested at 0.0%, 2.35%, 4.20% and 6.10% flour based on weight of banana pulp. Results of the physico-chemical and sensory evaluation showed that substitution at 2.35% and 4.20% level were suitable as base materials for catsup. However, 4.20% level of substitution gave a higher yield. Therefore, in terms of maximizing the utilization of banana flour, 4.20% banana flour substitution was found to be the best. Samples of banana catsup with 0.0% and 4.20% banana flour were stored at 37.8°C for accelerated storage to simulate prolonged storage conditions at room temperature. Both samples showed deterioration in physico-chemical attributes at the end of the third week with the sample containing 4.20% banana flour showing the most deterioration.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Bananas; Ketchup